City Development Strategy : Peshawar, Volume 1. Main Report - Peshawar City District (World Bank, Washington, DC, 2012)
The newly delineated Peshawar City District (PCD) has undergone significant transformations in the past ten years. Originally encompassing the adjoining districts of Charsadda and Nowshera, the district gradually shrunk in size after both sub-divisions acquired a district status of their own in the mid-nineties. However, as the provincial capital, Peshawar continues to enjoy a special status within North West Frontier Province (NWFP). It houses the provincial parliament, headquarters of all provincial public sector agencies, major Banks, Development Finance Institutions (DFls), academic institutions, Non-Government Organizations (NGOs), industry, various trading houses, and major private sector institutions. Over two million people co-exist in Peshawar in an environment that is marked by a high incidence of poverty, unemployment, poor access to quality social services, alarming levels of air and water pollution, and a worsening law and order situation. Their aggregate effect is that Peshawar has not only become a less desirable city from the perspective of the common citizenry, but more importantly, from the perspective of the local and international business community, that is so critical for its long-term growth. Rapid changes in the federal and the provincial governments have also adversely impacted on systems of governance. As a result, the development environment is characterized by a high degree of politicization, adhoc policies, inadequate planning, poor accountability, and generally weak capacities.